Analysis of External and Internal Factors Causes of Student Learning Difficulties and Their Relation to Biology Learning Outcome in MAN 3 Padang - Rani Purnama Sari; Lisa Deswati (Universitas Veteran Bangun Nusantara Sukoharjo, 2023)
This study aims to determine the external factors and internal factors that cause learning difficulties and their relationship with the learning outcomes of Biology class XI IPA MAN 3 Padang. The change in the online learning process to offline learning since the Covid-19 pandemic has had an impact on external factors and internal factors that cause learning difficulties that affect student learning outcomes. This type of research is descriptive with quantitative research methods. The study was carried out at MAN 3 Padang with a population of 165 students of class XI science who were registered in the even semester of the academic year 2021/2022, with a sample of 33 students. The sampling technique is random sampling, which is done randomly, using an error rate of 5%. Data collection in this study used a questionnaire containing statements of external factors and internal factors of students' learning difficulties using a Likert scale, and documents on students' learning outcomes for Biology in the even mid-semester exams for the 2021/2022 academic year. From the results of the study, it is known that the level of learning difficulties for external factors obtained an average value of 3.52 in the high category, while the level of learning difficulties for internal factors had an average value of 3.26 in the high category. The results of the Pearson product moment correlation test using the SPSS 20 program obtained a value on the external factor of 0.073 which is strongly correlated and the form of the relationship is negative and the internal factor has a value of 0.910 which is perfectly correlated with the negative relationship between external factors and internal factors with Biology learning outcomes in students. class XI IPA MAN 3 Padang. The results of the t test showed that the external factor tcount was -1.853 and the internal factor tcount was -113 indicating that there was no influence of external factors and internal factors (X) on students’ Biology learning outcomes (Y).